2014
DOI: 10.1186/2046-9063-10-6
|View full text |Cite
|
Sign up to set email alerts
|

The Manx shearwater (Puffinus puffinus) as a candidate sentinel of Atlantic Ocean health

Abstract: IntroductionSeabirds have been historically used to monitor environmental contamination. The aim of the present study was to test the suitability of a species belonging to the Procellariiformes group, the Manx shearwater, Puffinus puffinus, as a sentinel of environmental health, by determining contaminant levels (trace metals and organochlorine compounds) from carcass tissues and by isolating Vibrio spp. and Aeromonas spp. from live specimens. To this end, 35 Puffinus puffinus carcasses wrecked on the north-ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 58 publications
(102 reference statements)
0
11
0
Order By: Relevance
“…(Fern andez-Delgado et al 2016) and a higher prevalence of V. cholerae in aquatic birds (Rodr ıguez et al 2010), compared with the present study. In a study conducted in the same region as the present research, V. alginolyticus, V. fluvialis and V. harveyi were also the most prevalent species in a range of animal hosts (Roges et al 2010), although the same was not reported by Cardoso et al (2014).…”
Section: A E S T U a R I A N U S V F U R N I S I I V G A Z O G E mentioning
confidence: 48%
See 2 more Smart Citations
“…(Fern andez-Delgado et al 2016) and a higher prevalence of V. cholerae in aquatic birds (Rodr ıguez et al 2010), compared with the present study. In a study conducted in the same region as the present research, V. alginolyticus, V. fluvialis and V. harveyi were also the most prevalent species in a range of animal hosts (Roges et al 2010), although the same was not reported by Cardoso et al (2014).…”
Section: A E S T U a R I A N U S V F U R N I S I I V G A Z O G E mentioning
confidence: 48%
“…; Cardoso et al . ). Birds, more specifically those that inhabit aquatic environments, have the ability to spread pathogenic bacteria to humans through faeces.…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…V . cholerae non-O1/non-O139 was isolated from cloacal swab samples of wild manx shearwater ( Puffinus puffinus ) that were caught in the north-central coast of Rio de Janeiro, Brazil [70]. In another survey that was conducted in the same place a few years later, Cardoso and colleagues [71] isolated and identified V .…”
Section: Introductionmentioning
confidence: 99%
“…shielding luminaries, restricting emissions in the shorter wavelengths, and reducing timing and intensity of lighting, as well as an enhancement of rescue programmes can already be conducted in those areas where fallout is concentrated (Rodríguez et al 2008, Rodríguez and Rodríguez 2009). Regarding at‐sea threats where there is no specific information, it seems reasonable to speculate that, as other shearwaters, plastic ingestion, oils spills, food depletion and interaction with fisheries could severely affect their populations (Cardoso et al 2014). Thus, a better knowledge on foraging areas during breeding, migration stopovers and wintering areas, is now needed to identify its marine threats.…”
Section: Discussionmentioning
confidence: 99%